Effect of the modified method of preoperative skin cleaning on prevention of surgical site infection (改良术野皮肤清洁方法预防手术部位感染的效果分析) - ZHANG Wenjun (章文军); ZHANG Mingyang (章明阳); LUO Xiaoping (罗小平) (中西医结合护理)
Objective To investigate the effect of the modified method of preoperative skin cleaning on prevention of surgical site infection(SSI). Methods A total of 1450 patients undergoing spinal surgery were divided into the study group (n=747)and the control group(n=713)According to the preference of surgeons on method of preoperative skin cleaning. The routine preoperative skin preparation was conducted in the control group, and a modified method of preoperative skin cleaning (Jifro hand sanitizer and disinfectant gel)was performed after routine skin preparation in the study group. Besides, 50 patients in the study group were randomly selected for measuring Colony Forming Units (CFU) in the surgical area before and after cleaning the surgical site, and effect of using Jifro hand sanitizer and disinfectant gel CFU in the surgical site was analyzed. Results The incidence of SSI in the control group was 1. 96% and the study group was 0. 67%, which was statistically significant difference (P < 0. 05). After cleaning the surgical site of 50 randomly selected patients, the CFU after cleaning was fewer than that before cleaning(P < 0. 05). Conclusion The preoperative combination of Jifro hand sanitizer and disinfectant gel can effectively reduce the SSI rate and CFU, which is worth promoting in clinical practice. (目的 探讨改良术野皮肤清洁方法预防手术部位感染(SSI)的效果。方法 选取脊柱外科手术患者1450例, 根据手术消毒前皮肤清洁方式不同分为研究组(n=747)和对照组(n=713), 对照组常规清洁手术部位, 观察组在对照组基础上采用 “洁肤柔”洗手液和消毒凝胶清洁手术部位。另外, 随机抽取研究组50例手术患者, 根据清洁前和清洁后的手术区域皮肤进行细菌学菌落数的检测, 分析采用“洁肤柔”洗手液和消毒凝胶对清洁手术部位菌落数的影响。结果 对照组SSI发生率为1. 96%, 研究组SSI发生率为0. 67%, 2组差异有统计学意义(P＜0. 05)。随机抽取研究组50例手术患者手术部位清洁前、后细菌学检测情况, 清洁后菌落数小于清洁前, 差异有统计学意义(P＜0. 05)。结论 术前联合使用“洁肤柔”抗菌洗手液和手消毒凝胶对手术部位进行皮肤清洁, 能有效降低SSI发生率和菌落数。)